Plasmonic absorption enhancement in organic solar cells by nano disks in a buffer layer - Kim, Inho; Jeong, Doo Seok; Lee, Taek Seong; Lee, Wook Seong; Lee, Kyeong-Seok (AMER INST PHYSICS, 2012)
We demonstrate using finite-difference-time-domain calculations that embedding Ag nano disks (NDs) in the buffer layers of thin P3HT:PCBM organic solar cells can enhance optical absorption in the active layers at specific wavelength range. We show that the aspect ratio of the NDs is a key parameter for strong plasmonic absorption enhancement. Two different plasmonic absorption bands are observed stemming from optical refractive index differences among the layers surrounding the NDs in the solar cell devices. One absorption band by the surface plasmon mode localized at the interface of indium tin oxide/ND, which is undesirable for plasmonic absorption enhancement in the active layer, become negligible as the aspect ratio of the diameter-to-height increased. The other absorption band by the dipole-like surface plasmon mode, which plays a main role in enhancing the absorption in the active layer, is spectrally tunable by adjusting the aspect ratio of the NDs. The influences of diameter, height, and coverage of the NDs on optical absorption in the active layer are discussed. Embedding the optimal size NDs in the buffer layer leads to the enhanced total absorption in the 50 nm thick active layer by 16% relative to that without the NDs, and the optical absorption keeps enhanced with increasing the active layer thickness up to 90 nm. However, further increases in the active layer thickness are detrimental to absorption enhancement, which is considered to be caused by destructive interference between scattered light by the NDs and incident light. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4722349]
Keywords: EFFICIENCY